PELATIHAN ASSESSMENT PEMBELAJARAN MENGGUNAKAN PROGRAM ITEMAN PADA PENDIDIK IPS DI KABUPATEN GARUT - Tetep Tetep; Eldi Mulyana; Triani Widyanti (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2018)
Assessment of learning is very important by a teacher. A good assessment will positively influence the performance of a teacher. Through assessment, teachers can find out how far students can achieve the required level of competence. During this time, school and national exam tests used multiple choice tests. It is important that a teacher has competence in analyzing the items of the problem he made. Because of this, Iteman program comes as an alternative assessment of learning to analyse problem items and other statistical data. The purpose of this dedication is to provide training assessment learning by using Iteman program to social studies teachers in Garut District. The method is to give a theory lecture and proceed with the training of the Iteman program. The results of the evaluation of this activity concluded that there is an increase in knowledge and skills on assessment of learning in social studies teachers in Garut District, as well as 80% of the teachers of social studies understand the application methods of Iteman program after practicing directly during training.